MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN TEKNIK INDEX CARD MATCH UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPA SISWA DIKELAS VII 5 SMP NEGERI 3 TAMBANG - Nurhasanah '; Wan Syafii; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to improve the activity and learning outcomes through the application of science students learning Discovery Learning model with Index Card Match techniques in class VII.5 SMP Negeri 3 Tambang on Biodiversity material Beings And Environmental Pollution. This research is a class act that is performed in 2 cycles in April to May 2016. The subjects were students of class VII.5 SMP Negeri 3 Tambang totaling 29 people comprising 15 men and 14 women. The parameters of this study is the Student Activities, Student Results consisting of Absorption and Mastery Learning Student and Teacher Activities. The average activity of students in the first cycle is 77.80% with the category enough on the second cycle increased to 92.45% in both categories. Student learning outcomes based on the average absorption in the first cycle is 78.79% and the second cycle increased to 86.20%. Mastery learning students in the first cycle is 82.75% and the second cycle increased to 93.10%. The average teacher activity in cycle I and II is 100% with a very good category. From the research results can be concluded that the application of learning models Discovery Learning Index Card Match technique can increase Activities and Learning Outcomes Science student in class VII.5 SMP Negeri 3 Tambang.Keywords: Model Discovery Learning, Iindex Card Match techniques, activities, learning outcomes